Pengaruh Pengembangan Karyawan Danmotivasi Kerja Terhadap Kinerja Karyawan (Fakultas Ekonomi Universitas Gresik, 2023)
Changes in organizational environment increasingly complex and competitive so that human resources are the main asset of any organization as employees determine the success of the organization in achieving organizational goals. The development of quality human resources to support the success of management in the development of employee motivation is also needed in order to achieve labor productivity and job satisfaction of subordinates. Employee performance is the result of work accomplished person or group of people, in order to obtain the right employees - truly qualified according to the needs of the organization, and therefore researchers interested in doing research in PO. Puspa Jaya, Bandar Lampung.Problems faced by PO. Puspa Jaya is a transition position of the conductor becomes very slow drivers and outcomes should have been more than achieved. This is an indication of employee development at PO. Puspa Jaya Bandar Lampung less going well, so formulated problems